WORKSHOP PENGEMBANGAN RPS DALAM PENYELENGGARAAN MATA KULIAH BLENDED LEARNING MELALUI PENDEKATAN CBT DAN PjBL - Rahmawati; Agusmuji Santoso; Johar Permana; Diding Nurdin; Cepi Triatna; Misnar; Silvi Listia Dewi (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2023)
This community service activity is motivated by the importance of a lecturer having the ability to prepare RPS which enables students to gain the ability to support the achievement of 21st century competencies. This community service activity aimed to increase the understanding of lecturers, especially lecturers within the scope of the Faculty of Teacher Training and Education (FKIP) Almuslim University to have sufficient knowledge and skills in developing RPS through the CBT and PjBL approaches, so that they can create collaborative and participatory classes in an effort to support the achievement of IKU 7 in Higher Education. The workshop was held offline and online for two days, attended by 10 participants. The workshop implementation method was in the form of lectures, exercises, mentoring and interactive discussions. The workshop activities ran smoothly and were successful and had a positive impact on lecturers within the scope of FKIP Almuslim University. The results of this workshop activity are expected to increase the achievement of IKU 7 PT, especially IKU 7 collaborative and participatory classes, where it is hoped that learning in class applies the case solving learning method (case method) and team-based projects (project-based learning). In order to be more optimal, it is recommended that further community service activities involve more participants representing lecturers from other faculties besides FKIP, both within the Almuslim University and other HEIs in Bireuen Regency and throughout Aceh Province.